2021
DOI: 10.1108/jfrc-01-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green growth on financial stability

Abstract: Purpose The international institutions, policymakers and governments are promoting green growth as a policy objective for global financial stability (FS) without sound empirical investigation. Therefore, the purpose of this study is to investigate whether the green economy would be successful in achieving its main objective i.e. stabilizing the world financial system because the investment stakes are too high for this green transition. Design/methodology/approach The study used the two-step system generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…1. Integrated accounting system with transactional management and strategic accounting Source: developed by the authors based on [10] But not always existing or foreign accounting and financial mechanisms, as the practice of the author's studies [15,16,17,18] have shown, work in the conditions of Ukraine. For the modern period, the most relevant mechanisms are those that transform the debt model of deficit financing of the economy into the necessary attraction of the necessary financial resources to ensure production, solve the problem of quality of life and economic growth [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Integrated accounting system with transactional management and strategic accounting Source: developed by the authors based on [10] But not always existing or foreign accounting and financial mechanisms, as the practice of the author's studies [15,16,17,18] have shown, work in the conditions of Ukraine. For the modern period, the most relevant mechanisms are those that transform the debt model of deficit financing of the economy into the necessary attraction of the necessary financial resources to ensure production, solve the problem of quality of life and economic growth [19].…”
Section: Resultsmentioning
confidence: 99%
“…An unusual analogy for the impact of greening processes on financial stability in the world is given by the authors Jadoon I., Mumtaz R., Sheikh J., Ayub U. and Tahir M., emphasizing the importance of investing in green energy on the financial performance of multinational corporations [10].…”
Section: Methodsmentioning
confidence: 99%
“…The authors Jadoon I., Mumtaz R., Sheikh J., Ayub U. and Tahir M. provide an unusual analogy of the impact of greening processes on financial stability in the world, emphasizing the importance of green energy investments on the financial performance of multinational corporations ( Jadoon, Mumtaz, Sheikh, Ayub, Tahir, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results emanating from the study revealed that energy transition affects the financial system through excessively fast investment in such areas as nuclear energy with a high proclivity of endangering the financial system through evident threats to the banking sector. Jadoon et al (2021), investigated the impact of financial stability on green growth considering that the investment stakes are too high for green transition. The study adopted panel estimation techniques with a focus on 90 countries covering the period 2010-2015.…”
Section: Literature Reviewmentioning
confidence: 99%